Kepatuhan Pembatasan Cairan Pada Pasien Hemodialisis - Herlina, Santi; Rosaline, Mareta Dea (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Hemodialysis is currently the most common choice to replace the role and function of the kidney that hasbeen damaged. One of the problems in hemodialysis patients is patient non-compliance in limiting fluidintake. Patient non-compliance in limiting fluid intake can lead to excess volume of fluid in the body whichresults in complications of chronic renal failure. This study examines the factors that influence fluidrestriction compliance. The study was conducted on 38 respondents who underwent hemodialysis at DrajatPrawiranegara Hospital, Serang Regency, Banten Province. The aim of this study was to identify factors thatmost influence hemodialysis patient adherence to fluid restrictions. This research method is a quantitativeapproach using a cross sectional design. To analyze the variables that affect the compliance of liquid wetting,the multivariate binary logistic regression test was used. The results showed that the variable that had themost influence on fluid restriction compliance was age with a P value of 0.048 and the largest OR comparedto other variables, so that it had the strongest relationship with fluid restriction compliance 1.190 times aftercontrolling for variables of marital status, occupation, BMI, length of time. hemodialysis, HD duration,behavior, attitude.